Vital signs 2007-2008 : the trends that are shaping our future - Assadourian, Erik (W.W. Norton & Company, 2007)
This report tracks and analyzes 44 trends that are shaping our future, and includes graphs and charts to provide a visual comparison over time. Categories of trends include: Food, Agricultural Resources, Energy and Climate, Global Economy, Resource Economics, Environment, Conflict and Peace, Communications and Transportation, Population and Society, and Health and Disease.